Bank Ownership and the Effects of Financial Liberalization : Evidence from India - Gupta, Poonam (IMF Working Papers; Working Paper ;, 2011)
Do financial sector reforms necessarily result in expansion of credit to the private sector? How does bank ownership affect the availability of credit to the private sector? Empirical evidence is somewhat mixed on these issues. We use the Indian experience with liberalization of the financial sector to inform this debate. Using bank-level data from 1991-2007, we ask whether public and private banks deployed resources freed up by reduced state preemption to increase credit to the private sector. We find that even after liberalization, public banks allocated a larger share of their assets to government securities than did private banks. Crucially, we also find that public banks were more responsive in allocating relatively more resources to finance the fiscal deficit even during periods when state pre-emption (measured in terms of the requirement to hold government securities as a share of assets) formally declined. These findings suggest that in developing countries, where alternative channels of financing may be limited, government ownership of banks, combined with high fiscal deficits, may limit the gains from financial liberalization.